The Effect of Multiple Hop And Jump Exercises on the Power of Leg Muscles of Volleyball Athletes at Pst Club Bengkulu City - Kumoro Mashum Adi Luhung (Sinar Sport Journal, 2021)
This study aims to determine whether there is an effect of Multiple Hop and Jump exercises on the leg muscle power of volleyball athletes at the PST club in Bengkulu City. This type of research is quantitative research with the research method used is a pure experimental method. The population of this study were all volleyball athletes at the Bengkulu City PST club as many as 20 people. The sampling technique in this study is total sampling. Total sampling is a sampling technique where the total population is less than 100 so that the entire population is used as the research sample, namely: 20 people consisting of 10 experimental groups and 10 control groups. The variables of this research are Multiple Hop and Jump exercises and leg muscle power for PST volleyball athletes in Bengkulu City. The data collection technique used a vertical jump test. The data analysis technique used was the t-test. Based on the results of the research above, it can be concluded that multiple hop and jump exercises affect the leg muscle power of volleyball athletes at the PST club in Bengkulu City. The increase in leg muscle power is seen in the comparison of the changes in the average pretest and posttest. From the data that has been obtained from both groups, the experimental group has a pretest result of 45.4 and an average posttest result of 51.1 with a difference of 5.7. The results of the control group with a pretest average of 42.3 and an average posttest result of 47 with a difference of 4.7. The results of tcount for the experimental group were 6.87 > ttable 1.833, while for the control group the results of tcount were 6.91 > ttable 1.833. Then the data from the pretest and posttest results from the two groups were declared significant. Thus the hypothesis which reads "Is there any effect of multiple hop and jump exercises on the leg muscle power of volleyball athletes at the Bengkulu City PST club", was accepted.